“Incommensurable Airspace”: Image of Russia in Travelogue of Maxim Nezvorov - O. V. Kublitskaya (Научный диалог)
This article analyzes the image of Russia in Maxim Nezvorov’s travelogue “Journey to Kazan, Vyatka, and Orenburg in 1800.” Based on theoretical frameworks, we identify three aspects of analysis: genre, spatiality, and subjectivity. The study employs structuraldescriptive and cultural-historical methods, alongside the foundational principles of N. L. Leiderman’s genre theory, V. L. Kagansky’s concept of cultural landscape, and B. O. Korman’s ideas on the subject of artistic text. Our findings indicate that the choice of a quasi-documentary epistolary form allowed the author to establish a commitment to authenticity, combined with a characteristically sentimental intention of the “sensitive traveler.” It is demonstrated that Nezvorov delineates a system-forming dichotomy of “centerperiphery,” within which the cultural landscape is (re)constructed. We conclude that the author evaluates a key component of this landscape — urban planning and architecture — while the landscape itself serves a supportive role. Nezvorov pays particular attention to the extraordinarily diverse ethnic composition of the empire’s population. Although he rarely grants his “interlocutors” a voice, their comments and judgments enable a partial reconstruction of the worldview of a person in the early 19th century, one of the key elements of which is the image of Russia.